Os bastidores da educação primária: criação e expansão das escolas isoladas rurais em municípios do interior paulista (1889 –1921) - Jesus, Adriana do Carmo de (Universidade Federal de São Carlos, 2018)
This work has as main objective to deal with the creation and expansion of isolated schools in the interior of São Paulo between the years 1889 to 1920 – the first 31 years of republic. The isolated schools were unidocent elementary education institutions that served at the same time and in the same space students of different ages and levels of knowledge. We understand that it was the economic development of the state of São Paulo started in the mid-nineteenth century - with the coffee-based agricultural expansion and accompanied by a railway network that linked cities and attracted a large population contingent – which made possible the emergence of a dynamic center in southeastern Brazil, especially in what we know today as Rio de Janeiro, Minas Gerais and São Paulo states, as well as the expansion of public schools in inland municipalities in the first decades of the 20th century. From this perspective, this period can be understood as a "watershed" in the organization of the free, secular and compulsory public education system. In these decades, schooling was, above all, part of a political program to solve Brazilian problems, so that it incorporated large sections of the population into the civilizing process. Political participation was linked not only to census voting but, to the process of schooling, however, this process already in the early years of the Republic did not mean a good school for all, especially in the state of São Paulo and to understand the expansion of elementary public schooling, it is necessary to understand the history of Brazilian education in the republican period, also understanding that the diffusion of the school groups was not established in a homogeneous, natural and linear way, as if we had first the isolated school that became schools reunited and sometime later the leaders realized that it was viable the transformation of these schools reunited in school group.
The backstage of primary education: creation and expansion of rural isolated schools in municipalities of the paulista interior (1889 -1921)
Keywords: Escola isolada; Escola rural; Educação primária paulista; Primeira República; Isolated school; Paulista elementary education; History education; First Republic; CIENCIAS HUMANAS::EDUCACAO